A review of the challenges and opportunities for restoring animal-mediated pollination of native plants. Issue 1 (18th June 2020) - Cariveau, Daniel P.; Bruninga-Socolar, Bethanne; Pardee, Gabriella L.
Abstract : Ecological restoration is increasingly implemented to reverse habitat loss and concomitant declines in biological diversity. Typically, restoration success is evaluated by measuring the abundance and/or diversity of a single taxon. However, for a restoration to be successful and persistent, critical ecosystem functions such as animal-mediated pollination must be maintained. In this review, we focus on three aspects of pollination within ecological restorations. First, we address the need to measure pollination directly in restored habitats. Proxies such as pollinator abundance and richness do not always accurately assess pollination function. Pollen supplementation experiments, pollen deposition studies, and pollen transport networks are more robust methods for assessing pollination function within restorations. Second, we highlight how local-scale management and landscape-level factors may influence pollination within restorations. Local-scale management actions such as prescribed fire and removal of non-native species can have large impacts on pollinator communities and ultimately on pollination services. In addition, landscape context including proximity and connectivity to natural habitats may be an important factor for land managers and conservation practitioners to consider to maximize restoration success. Third, as climate change is predicted to be a primary driver of future loss in biodiversity, we discuss the potential effects climate change may have on animal-mediated pollination within restorations. An increased mechanistic understanding of how climate change affects pollination and incorporation of climate change predictions will help practitioners design stable, functioning restorations into the future.